EXPLORING THE ROLES OF TWO INDONESIAN EFL NOVICE TEACHERS IN AN ONLINE-BASED LEARNING ENVIRONMENT - Mutiara Putri Aulia, - (2022)
Due to COVID-19 pandemic, the learning process at Indonesian schools has changed into online mode. In the process of online learning activity, teachers are required to deliver the learning materials through online equipment. Thus, teachers need to select appropriate roles to help students in understanding the learning materials. Numerous researchers have focused on online learning issue as the main topic of their study. However, this study is aimed to specifically explore two EFL novice teachers' roles in online learning environment and how they adjust the roles based on their perspective using theories adapted from Alvarez, et. al (2009) about online instructors' roles and Harmer (2007) about the roles of teachers in a classroom. Two novice teachers were selected to participate in this qualitative case study because their perspectives in performing teachers' roles based on their short-time teaching experience are necessary to explore. Data of the study were derived from online classroom observation, field notes and interviews. The triangulated results show that, within limited activities, both EFL novice teachers are still capable of performing designer, social and cognitive roles which are supported by their technological and managerial competences. To adjust their roles in online teaching environment, the participating teachers tend to add and modify some teaching actions in the online classes.